KINDS OF FRIENDSHIP IN JAMES DASHNER’S NOVEL THE DEATH CURE - Dewan Septian; Pardi Pardi (JOURNAL OF LANGUAGE, 2022)
The aim of this study is to analyze the kinds of friendship in James Dashner’s novel The Death Cure. Most importantly, true friendship stands for a relationship free of any judgments. In a true friendship, a person can be themselves completely without the fear of being judged. It makes you feel loved and accepted. This kind of freedom is what every human strives to have in their lives. The data are taken from the novel by using descriptive analysis. The method used is descriptive qualitative method. The results show that there are three kinds of friendship found in the novel. They are friendship of utility, friendship of pleasure and friendship of virtue. Friendship of utility gives the protagonist an advantage in finding the cure. Friendship of pleasure brings the protagonist happiness in life. Meanwhile, friendship of virtue gives the protagonist a convenient life. A good friendship should give a comfortable feeling and form better human beings.